Blood markers of inflammation and endothelial dysfunction in cardioembolic stroke: systematic review and meta-analysis. (19th May 2017) - Piccardi, Benedetta; Giralt, Dolors; Bustamante, Alejandro; Llombart, Victor; García-Berrocoso, Teresa; Inzitari, Domenico; Montaner, Joan
Abstract: Context: Various processes including inflammation and endothelial dysfunction have been implicated in the pathogenesis of cardioembolic (CE) strokes. Objective: To review the evidence and investigate the association between immune-inflammatory biomarkers and CE strokes versus other stroke subtypes. Methods: We systematically reviewed the literature (sources: MEDLINE, web-based registerhttp://stroke-biomarkers.com, reference lists) with quality assessment and meta-analysis of selected articles. Results: The most consistent association was found between C-reactive protein (CRP) and CE strokes when compared to other stroke subtypes (standardized mean difference 0.223 (0.116, 0.343); p < 0.001) Conclusions: Our findings confirm a possible association between selected inflammatory biomarkers and CE stroke.